Ten Years and Counting: Preserving and Sharing Colorado's Agricultural History Online. Issue 3 (3rd July 2019) - Watson, Renae J.; Level, Allison V.; Oehlerts, Beth
Abstract: Colorado State University Libraries (CSUL) support the preservation of agricultural history, as evidenced by their participation in the Preserving the History of United States Agriculture and Rural Life: State and Local Literature, 1820–1945 project, administered by Cornell University. This article reviews CSUL's work on this preservation project, including digitization of historical agriculture-related documents. CSUL's latest effort to keep agricultural literature relevant and accessible includes moving the Colorado Agriculture Bibliography website to Springshare's LibGuides platform (https://libguides.colostate.edu/agbib ). Advantages and challenges of using the LibGuides platform for the promotion and sharing of such collections are discussed.